TA'ARUF LOCALITY: INTEGRATION OF ISLAMIC LAW AND CUSTOMARY LAW OF THE PHENOMENON USING TRIBE GREDOAN IN BANYUWANGI - Ainiyah, Qurrotul (IAIN LANGSA, 2019)
This research is a study which used a qualitative approach with the type field research, which is related to the Gredoan tradition as the event of looking for a life partnerin using community located on Macan Putih Village, Kabat district in banyuwangi. In thispaper will explain how is the custom to find a mate in Banyuwangi society that has lastedsince long ago. Gredoan is the relations between customary law and Islamic law whichseeks to integrate between the customary laws with Islamic law in matters of marriage. theContributions of research are: First, there is public space in the form of practice the ta'arufprocess towards marriage in Banyuwangi Using society which known as gredoan custom.Second, that Islamic law turns out to have spaces to accommodate the customs as the jointsof Islamic law. gredoan Tradition as an al-?urf in using community of banyuwangi inta'aruf process towards marriage, it obtains legitimacy by the maq??id al-syar??ah which isbased on the rules is al-âdat al-Muhakkamah.